Evaluating the effectiveness of a new curriculum for transcultural nursing education: a mixed-method study - Betül Tosun; Emel Bahadır Yılmaz; Ezgi Dirgar; Eda Başustaoğlu Şahin; Kadiriye Pehlivan Hatipoğlu; Ayla Yava (BMC, 2024)
Abstract Background In recent years, limited studies have evaluated the development of cultural awareness, sensitivity, skills, communication and competence among nursing students using different models and curricula. Objectives This study aimed to evaluate the effectiveness of a new internationally developed curriculum for transcultural nursing education. Methods This mixed methods study was conducted on nursing students (n = 83) who attended a transcultural nursing course from 2021 to 2022 during the fall semester. A paired samples test was used to compare total scores, and the related-samples Wilcoxon signed-rank test was used to compare subscale scores. Results The vast majority (94.0%) of the participants mentioned Islam as their religion. Turkish was the mother tongue of 91.6% of them, while 10.8% were able to speak English and 6.0% were able to speak Kurdish fluently. The mean score for the achievement of cultural competence subdimension posttest was significantly greater (p < 0.001). Posttest mean scores for challenges and barriers in providing culturally competent care subdimensions were significantly lower (p = 0.003). The mean score on the culturally sensitive communication subdimension pretest was 21.00 ± 4.76, and the mean score on the posttest increased to 23.02 ± 6.05, which was a statistically significantly greater difference (p = 0.024). According to the qualitative results of our study, five main themes were analyzed: transcultural nursing as an opportunity, transcultural nursing as a didactic process, transcultural nursing as a professional field, transcultural care as a safe environment, and transcultural care as an obligation. Conclusions In this study, after a semester of continuing education, nursing students developed respect for cultural diversity, cultural competence, and culturally sensitive communication.